II. Abdülhamid dönemi kara harp sanayii (1876-1908) - Tetik, Fatih (My University, 2017)
19. yüzyılın ortalarından itibaren ateşli silahlar teknolojisindeki global dönüşüm, savaş organizasyonu ve harp sanayi sektöründeki imalat yapısını değişmeye zorlamış ve pek çok ülke bu yeni silah teknolojisi ve üretim modeline ayak uydurmak zorunda kalmıştı. Osmanlı Devleti de gerek düzenli bir istihbarat ağı ile son teknik gelişmelerden haberdar olma ve gerek teknoloji transferi ile yeni silahları yerli işletmelerde üretebilmek için bu değişimlere intibak etmeye çalıştı. Bu nyanın etkilendiği bu teknolojik dalganın nelerden ibaret olduğu ve Osmanlı Devleti’nin yeni üretim tekniklerine adaptasyon sürecini anlamaya yöneliktir.

From the middle of the 19th century, the transformation of firearms technology forced changes in the organization of war and the structure of the production of war industry; most countries had no choice but to follow this new model of production and and construct these new forms of firearm technology. The Ottoman Empire attempted to follow these transformations as well, both to keep the organized intelligence services up to date in recent technical developments and also in order to manufacture firearms at factories within the Empire. This doctoral dissertation is an attempt to understand this global technological shift and the process by which new manufacturing technology was adapted within the Ottoman Empire.
Keywords: army; Baruthane; defence industry; Fişekhane; Güvenlik Stratejisi; istihbarat; military; military industry; ordu; Osmanlı ordusu; Ottoman Army; Savunma sanayi; silah; Silah endüstrisi; Tarih; Tarih, Askeri; technology; Teknoloji Takibi; Teknoloji Transferi; Tophane; tüfek; Tüfekhane; Türkiye